2022
DOI: 10.1002/jmv.27580
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mutations and lineages of SARS‐CoV‐2 virus in the early phase of COVID‐19 pandemic and subsequent 1‐year global expansion

Abstract: A novel coronavirus, SARS‐CoV‐2, has caused over 274 million cases and over 5.3 million deaths worldwide since it occurred in December 2019 in Wuhan, China. Here we conceptualized the temporospatial evolutionary and expansion dynamics of SARS‐CoV‐2 by taking a series of the cross‐sectional view of viral genomes from early outbreak in January 2020 in Wuhan to the early phase of global ignition in early April, and finally to the subsequent global expansion by late December 2020. Based on the phylogenetic analysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…To validate the results obtained from the Pearson correlation, the hierarchical clustering technique was applied; this method groups similar objects together. Since highly frequent mutations tend to play a critical role in the evolution of the virus ( 17 ), the 25 most significant mutations that were present in more than 10% of the genomes were tested for similarity using the hierarchical clustering technique. The figure_factory method from the plotly library of Python was used to perform the hierarchical clustering on the binary matrix of the 25 most significant mutations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To validate the results obtained from the Pearson correlation, the hierarchical clustering technique was applied; this method groups similar objects together. Since highly frequent mutations tend to play a critical role in the evolution of the virus ( 17 ), the 25 most significant mutations that were present in more than 10% of the genomes were tested for similarity using the hierarchical clustering technique. The figure_factory method from the plotly library of Python was used to perform the hierarchical clustering on the binary matrix of the 25 most significant mutations.…”
Section: Methodsmentioning
confidence: 99%
“…They identified 3037C>T as the most frequent mutation, as it occurred in 98% of isolates. Though synonymous, this mutation was shown to co-occur with 3 other mutations, including 241C>T, 14408C>T, and 23403A>G. In another study, Chen et al ( 17 ) analyzed 261,323 sequences of SARS-CoV-2 from across the globe to study the evolution of the virus. The authors observed that the initial SARS-CoV-2 M genotype ignited the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing coronavirus disease 2019 (COVID-19) pandemic is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus [ 1 ]. Ever since the initial SARS-CoV-2 outbreak in early December 2019, high-frequency mutations in SARS-CoV-2 have altered the infectivity of the virus and led to the emergence of a variety of SARS-CoV-2 variants, including Alpha, Beta, Gamma, Delta, Kappa, and Omicron [ 2 , 3 ]. As of January 2023, approximately 662 million confirmed COVID-19 cases and more than 6.7 million deaths have been reported worldwide [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past research found persons with specific affective temperament types (depressive, cyclothymic, hyperthymic, irritable, and anxious) prone to adverse clinical outcomes such as higher suicide behavior [ 16 , 17 ]. For these reasons, the impact of COVID-19 on mental health is becoming an increasing concern among policymakers and health practitioners, particularly in the face of multiple waves of infections and longer and more intensive SIPOs measures adopted by Governments [ [18] , [19] , [20] ]. Equally important but not fully explored in terms of research is understanding coping strategies (positive and negative) used by citizens to manage the social isolation and distress that come with prolonged lockdowns [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%